Possible synergy effect of hydrogen sulfide and acetate produced by sulfate-reducing bacteria on inflammatory bowel disease development - Kushkevych, Ivan (J Adv Res, 2020)
INTRODUCTION: Increased numbers of sulfate-reducing bacteria (SRB) are often found in the feces of people and animals with inflammatory bowel disease. The final products of their metabolism are hydrogen sulfide and acetate, which are produced during dissimilatory sulfate reduction process. OBJECTIVES: The aim of the study was to monitor processes concerning sulfate reduction microbial metabolisms, including: the main microbial genera monitoring and their hydrogen sulfide production in the intestines of healthy and not healthy individuals, phylogenetic analysis of SRB isolates, cluster analysis of SRB physiological and biochemical parameters, SRB growth kinetic parameters calculation, same as the application of the two-factor dispersion analysis for finding relationship between SRB biomass accumulation, temperature and pH. Feces samples from healthy people and patients with colitis were used for isolation of sulfate-reducing microbial communities. METHODS: Microbiological, biochemical, biophysical, molecular biology methods, and statistical processing of the results have been used for making an evaluation of gained results. RESULTS: Two dominant SRB morphotypes differed in colony size and quantitative ratio in the feces of healthy and colitis patients were observed and identified. In the feces of healthy people, 93% of SRB of morphotype I prevailed (Desulfovibrio) while morphotype II made only 7% (Desulfomicrobium); in the feces of patients with colitis, the ratio of these morphotypes was 99:1, respectively. Hydrogen sulfide concentrations are also higher in the feces of people with colitis and certain synergy effects exist among acetate produced by SRB. CONCLUSIONS: The study results brought important findings concerning colony environments with developed colitis and these findings can lead to the development of possible risk indicators of ulcerative colitis prevalence.